Influenza A(H1N1)pdm09 Virus in Pigs, Réunion Island - Cardinale, Eric (Centers for Disease Control and Prevention, 2012)
During 2009, pandemic influenza A(H1N1)pdm09 virus affected humans on Réunion Island. Since then, the virus has sustained circulation among local swine herds, raising concerns about the potential for genetic evolution of the virus and possible retransmission back to humans of variants with increased virulence. Continuous surveillance of A(H1N1)pdm09 infection in pigs is recommended.